2015
DOI: 10.2131/fts.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fish oil on cytochrome P450 3A expression in the liver of SHR/NDmcr-cp (<i>cp</i>/<i>cp</i>) rats, an animal model for metabolic syndrome

Abstract: Pathophysiological and nutritional conditions often affect the expression of drug-metabolizing enzymes. SHR/NDmcr-cp (cp/cp) rats (SHR/NDcp) are highly suitable as a metabolic syndrome (MS) model. Nevertheless, little is known about the expression profile of cytochrome P450 (CYP) in the liver of SHR/NDcp. We thus attempted to clarify the expression profile of CYP genes and the effect of fish oil (FO) on this profile in the liver of SHR/NDcp. Lower levels of CYP3A2 mRNA and CYP3A activity (testosterone 6β-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Previous study suggested the intake of sh oil at a high dose up-regulated CYP3A2 gene expression and CYP3A activity in liver. 29 Fish oil was also proved to increase the activities of CYP1A1 and CYP3A1 containing drug-metabolizing capacity. 30 FMO was similar to cytochrome P450 (CYP) in the aspects including the location, co-factor requirement and activity toward xenobiotics.…”
Section: Effects Of Sh Oil On Fmos Gene Expressions and Enzyme Activmentioning
confidence: 99%
“…Previous study suggested the intake of sh oil at a high dose up-regulated CYP3A2 gene expression and CYP3A activity in liver. 29 Fish oil was also proved to increase the activities of CYP1A1 and CYP3A1 containing drug-metabolizing capacity. 30 FMO was similar to cytochrome P450 (CYP) in the aspects including the location, co-factor requirement and activity toward xenobiotics.…”
Section: Effects Of Sh Oil On Fmos Gene Expressions and Enzyme Activmentioning
confidence: 99%